2014
DOI: 10.1002/qj.2377
|View full text |Cite
|
Sign up to set email alerts
|

On the formation and maintenance of the stratospheric surf zone as inferred from the zonally averaged potential vorticity distribution

Abstract: The diagnostic relation between eddy potential vorticity flux and Eliassen–Palm flux convergence in the transformed Eulerian mean shallow‐water system is used to infer the flux convergence needed to establish a stratospheric surf zone comprising a single region of perfectly homogenized potential vorticity, or to maintain the surf zone in steady state against the restoring effect of radiative relaxation. In the transient case, and when wave breaking is assumed to mix potential vorticity on time‐scales shorter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The consistency we have found between the planetary wave responses to applied torques and ray theory is in accordance with previous studies that have shown that ray theory appears to be successful at explaining the tropospheric response to lower stratospheric heating (Simpson et al 2009) and the extratropical stratospheric response to QBO forcing (Garfinkel et al 2012). This provides evidence that ray theory is generally useful for understanding the responses to applied forcings in the stratosphere (though this does not preclude other frameworks from also being useful, such as the non-linear approach of O'Neill and Pope (1988), or the PV-based approaches of Cohen et al (2014) and Scott and Liu (2014)).…”
Section: Fig 18mentioning
confidence: 93%
“…The consistency we have found between the planetary wave responses to applied torques and ray theory is in accordance with previous studies that have shown that ray theory appears to be successful at explaining the tropospheric response to lower stratospheric heating (Simpson et al 2009) and the extratropical stratospheric response to QBO forcing (Garfinkel et al 2012). This provides evidence that ray theory is generally useful for understanding the responses to applied forcings in the stratosphere (though this does not preclude other frameworks from also being useful, such as the non-linear approach of O'Neill and Pope (1988), or the PV-based approaches of Cohen et al (2014) and Scott and Liu (2014)).…”
Section: Fig 18mentioning
confidence: 93%
“…To make clear the area-preserving nature of the perturbations, we have used ( c ) 2 ∝ 2 as the horizontal coordinate, the cylindrical equivalent of the coordinate = sin typically used in spherical geometry. While clearly a gross oversimplification, the profiles nevertheless capture the basic stratospheric wave guides of the vortex edge and subtropical flank of the surf zone (Juckes and McIntyre, 1987;Polvani et al, 1995;Scott and Liu, 2015).…”
Section: Model Descriptionmentioning
confidence: 93%
“…While clearly a gross oversimplification, the profiles nevertheless capture the basic stratospheric wave guides of the vortex edge and subtropical flank of the surf zone (Juckes and McIntyre, ; Polvani et al . ; Scott and Liu, ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…For q 0 thus defined, h e is obtained from Eq. assuming axisymmetry, vanishing δ and no topography, by the iterative method described in Scott and Liu (). The potential vorticity and the associated zonal wind and height profiles are as shown in Figure (a).…”
Section: Model and Experimental Designmentioning
confidence: 99%